Serum and peritoneal exudate concentrations after high doses of β-lactams in critically ill patients with severe intra-abdominal infections: an observational prospective study. (10th October 2019) - Leon, Lisa; Guerci, Philippe; Pape, Elise; Thilly, Nathalie; Luc, Amandine; Germain, Adeline; Butin-Druoton, Anne-Lise; Losser, Marie-Reine; Birckener, Julien; Scala-Bertola, Julien; Novy, Emmanuel
Abstract: Background: Critically ill patients with severe intra-abdominal infections (IAIs) requiring surgery may undergo several pharmacokinetic (PK) alterations that can lead to β-lactam underdosage. Objectives: To measure serum and peritoneal exudate concentrations of β-lactams after high doses and optimal administration schemes. Methods: This observational prospective study included critically ill patients with suspicion of IAI who required surgery and a β-lactam antibiotic as empirical therapy. Serum and peritoneal exudate concentrations were measured during surgery and after a 24 h steady-state period. The PK/pharmacodynamic (PD) target was to obtain serum β-lactam concentrations of 100% fT >4×MIC based on a worst-case scenario (based on the EUCAST highest epidemiological cut-off values) before bacterial documentation ( a priori ) and redefined following determination of the MIC for the isolated bacteria ( a posteriori ) . Registered with ClinicalTrials.gov (NCT03310606). Results: Forty-eight patients were included with a median (IQR) age of 64 (53–74) years and a SAPS II of 40 (32–65). The main diagnosis was secondary nosocomial peritonitis. Piperacillin/tazobactam was the most administered β-lactam antibiotic (75%). The serum/peritoneal piperacillin/tazobactam ratio was 0.88 (0.64–0.97) after a 24 h steady-state period. Prior to bacterial documentation, 16 patients (33.3%) achieved the a priori PK/PD target. The identification of microorganisms was available for 34 patients (71%). Based on the MIC for isolated bacteria, 78% of the patients achieved the serum PK/PD target. Conclusions: In severe IAIs, high doses of β-lactams ensured 100% fT >4×MIC in the serum for 78% of critically ill patients with severe IAIs within the first 24 h. In order to define optimal β-lactam dosing, the PK/PD target should take into account the tissue penetration and local ecology.